2021
DOI: 10.7759/cureus.16325
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Outcomes Associated With Early Versus Late Tracheostomy From a National Standpoint

Abstract: Tracheostomy is a procedure that is commonly used in critically ill patients who require prolonged mechanical ventilation due to acute respiratory failure or airway problems. The best tracheostomy timing (early vs. late) and techniques (percutaneous dilatational, other new percutaneous procedures, open surgery) have been hotly debated. This research aimed to evaluate the outcome of early versus late tracheostomy in terms of in-hospital mortality, patient length of stay in the hospital, and cost after a detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Additionally, patients should be extubated as appropriate. If unable to extubate, early tracheostomy should be considered as this helps to wean sedation, improve oral care, and reduce the incidence of vocal cord damage as a result of trans laryngeal endotracheal intubation [42].…”
Section: Mechanical Ventilation Managementmentioning
confidence: 99%
“…Additionally, patients should be extubated as appropriate. If unable to extubate, early tracheostomy should be considered as this helps to wean sedation, improve oral care, and reduce the incidence of vocal cord damage as a result of trans laryngeal endotracheal intubation [42].…”
Section: Mechanical Ventilation Managementmentioning
confidence: 99%
“…The timing of tracheotomy in COVID-19 patients is still debatable, and contrasting results have been published. Findings from single-center studies revealed; early tracheostomies [23][24][25] decrease the duration of mechanical ventilation and increase ventilator liberation rates by facilitating a faster weaning process and decreasing the length of hospitalization. Nevertheless, some centers tend to postpone tracheostomies as much as possible due to the high risk of aerosolization.…”
Section: Figure 3: Illustration Of Outcomes and Complications Post-su...mentioning
confidence: 99%
“…6 The high complication rate is due to adverse events such as surgical site infection, hemorrhage, pneumothorax, tracheoesophageal fistula, and systemic complications; this could potentially cause tracheostomies to be resource-intensive procedures, with the average amount of hospital charges associated with tracheostomy costing about $265,000. 7,8 Patients and their families have been demonstrated to receive inadequate information regarding long-term complications during tracheostomy decision-making. 9 Easy-tounderstand risk stratification tools can help physicians communicate the consequences of tracheostomies to patients and patients' families.…”
mentioning
confidence: 99%
“…As tracheostomies are performed for severe illnesses and situations, the peri‐ and postoperative complication rate for tracheostomies can be as high as 45% 6 . The high complication rate is due to adverse events such as surgical site infection, hemorrhage, pneumothorax, tracheoesophageal fistula, and systemic complications; this could potentially cause tracheostomies to be resource‐intensive procedures, with the average amount of hospital charges associated with tracheostomy costing about $265,000 7,8 …”
mentioning
confidence: 99%